Persepsi Pemustaka Terhadap Ketersediaan Koleksi di Perpustakaan Pascasarjana Universitas Negeri Padang - Sari, Widya Novita; Ardoni, Ardoni (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
The aim of this research is to; (1) to describe how users perceive the availability of collections and the relevance of collections in the Padang State University Postgraduate Library; (2) to describe how users perceive the availability of user-oriented collections in the Padang State University Postgraduate Library; (3) to describe the user's perception of the availability of collections in terms of the completeness of the collection at the Padang State University Postgraduate Library; (4) to describe how users perceive the availability of collections from the latest collections in the Padang State University Postgraduate Library. This research uses quantitative descriptive methods. The population in this study was 2,714 users. The sampling technique used in this research was simple random sampling, which was taken to represent the population, then the sample size was 96 people. Based on the results of the data analysis carried out, it shows that there are library perceptions regarding the availability of collections with four indicators with an average of 2.92 in the positive category. (1) the collection relevance indicator shows that the average score is 3.00. This score is in the range of 2.51-3.25 which indicates a positive level of satisfaction. This is proven that in the view of the library the available collections are relevant to their needs; (2) This user-oriented indicator obtained an overall average of 2.91. This score is in the interval 2.51-3.25, indicating a positive level. So it is proven that users at the Padang State University Postgraduate library feel that the collections available in the library are in accordance with their information needs; (3) Indicators of the completeness of this collection obtained an overall average score of 2.90. This score is in the range of 2.51-3.25, indicating a positive level of satisfaction. From the results of the data scores, it shows that visitors to the Padang State University Postgraduate library said that the collections available in the library were complete; (4) the collection recency indicator shows that the overall average score is 2.87. This score is in the range of 2.51-3.25, indicating a positive level of satisfaction. From the data obtained, it shows that visitors to the Padang State University library said that the collections available were up to date and up to date in line with current developments.